2010
DOI: 10.1111/j.1600-0714.2010.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Notch signaling in human tongue carcinoma

Abstract: Expressions of Notch receptors and ligands in tongue carcinoma and adjacent non-neoplastic tongue tissues suggest that Notch signaling may control cell differentiation and proliferation of carcinoma cells. The disorder of Notch signaling may be a mechanism of the tongue carcinoma development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 38 publications
(58 reference statements)
4
74
1
8
Order By: Relevance
“…In previous studies, the overexpression of Notch1 and its ligands has been observed in OSCC specimens. 34,35 However, a recent study demonstrated opposite results to this study. The study of Sakamoto et al 24 showed similar Notch1 expression to that observed in our study in normal tissues, whereas their results for dysplastic and cancerous tissues were different, and Notch1 was downregulated in the neoplastic lesions.Although the antibodies against Notch1 and staining method used in our study were different from those used by Sakamoto et al, 24 our immunohistochemical staining results showed clear and specific membranous staining.…”
Section: Discussioncontrasting
confidence: 53%
“…In previous studies, the overexpression of Notch1 and its ligands has been observed in OSCC specimens. 34,35 However, a recent study demonstrated opposite results to this study. The study of Sakamoto et al 24 showed similar Notch1 expression to that observed in our study in normal tissues, whereas their results for dysplastic and cancerous tissues were different, and Notch1 was downregulated in the neoplastic lesions.Although the antibodies against Notch1 and staining method used in our study were different from those used by Sakamoto et al, 24 our immunohistochemical staining results showed clear and specific membranous staining.…”
Section: Discussioncontrasting
confidence: 53%
“…Of particular interest is NOTCH1, the second most commonly mutated gene in HNSCC after p53 [22,23]. NOTCH1 is over-expressed in HNSCC relative to normal tissue [21,[24][25][26][27]. Evidence for the role of NOTCH1 in angiogenesis is preliminary, and to our knowledge no studies have made direct comparison between NOTCH1 and VEGF or EGFR.…”
Section: Introductionmentioning
confidence: 99%
“…7,26 It has recently been demonstrated that Notch1 mutations are frequently found in HNSCC, suggesting a potential role for this pathway in the biology of CSCs and in the etiology of head and neck cancer. 13 Zhang et al 27 reported high expression levels of Notch receptors and ligands in tongue cancer and suggested that Notch signaling may control the differentiation and proliferation of tongue carcinoma cells. Zeng et al 10 reported that HNSCC may utilize the Notch signaling pathway to promote tumor angiogenesis in vivo, and that the level of Jagged1 expression is associated with the development of 9 reported that Notch1 expression is associated with cisplatin resistance in HNSCC.…”
Section: Notch1 Expression Can Predict the Prognosis Of Patients Withmentioning
confidence: 99%